The levels of inflammatory, angiogenic, and stress biomarkers in plasma of donors depending on anti-SARS-CoV-2 IgG titers - D.I. Krenytska; V.L. Karbovskyy; Ludovico Abenavoli; T.M. Falalyeyeva; Giuseppe Guido Maria Scarlata; N.G. Raksha; T.B. Vovk; L.I. Kot; O.M. Savchuk; Maria Luisa Gambardella; O.I. Kovalchuk; V.I. Pankiv; et al. (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, has led to widespread illness and global health challenges. While the acute phase of the infection has been extensively studied, the long-term effects, particularly in individuals who have recovered, remain unclear. Post-acute complications of SARS-CoV-2 involves prolonged symptoms and systemic disorders, including persistent inflammation, endothelial dysfunction, and immune dysregulation, which often last for months. Among the key factors contributing to these conditions, there are pro-inflammatory cytokines, growth factors involved in angiogenesis, hypoxia-inducible and stress-related proteins, which play a significant role in tissue repair and immune response modulation. The research aimed to evaluate the degree of inflammation, to determine the levels of pro-angiogenic factors, сellular hypoxia marker HIF-1α, and heat shock proteins, such as HSP60 and HSP70, in plasma of healthy donors who have recovered from COVID-19, with a particular focus on the relationship between the levels of these biomarkers and anti-SARS-CoV-2 IgG titers. Materials and methods. This research involved donors between the ages of 25 and 45 years, who had recovered from COVID-19 at least 3 to 6 months prior to the beginning of the study. All patients were divided into groups based on their anti-SARS-CoV-2 IgG titers. The plasma levels of inflammatory TNF-α, transcription factor NF-κB, angiogenic factors VEGF, PDGF and FGF-2, hypoxic factor HIF-1α, and heat shock proteins were measured by enzyme-linked immunosorbent assay. Group differences were analyzed using ANOVA with Tukey’s test or Kruskal-Wallis with Dunn’s test, presenting results as median and interquartile range, with significance at p ≤ 0.05. Results. The study found significant differences in the plasma levels of the analyzed parameters among donor groups with varying anti-SARS-CoV-2 IgG titers. There was an increase in pro-inflammatory markers, such as TNF-α and NF-κB, in plasma of donors with higher anti-SARS-CoV-2 IgG titers. The levels of angiogenic VEGF, PDGF, and FGF-2 showed distinct patterns, with VEGF levels generally reduced, except in the group of donors with titers of 95 ± 5 and 125 ± 10 Index (S/C), where they significantly increased. PDGF and FGF-2 levels were notably higher in groups of donors with titers of 95 ± 5 and 175 ± 10 Index (S/C). HIF-1α levels also increased significantly in plasma of donors with anti-SARS-CoV-2 IgG titers of 75 ± 5 and 175 ± 10 Index (S/C) compared to those without anti-SARS-CoV-2 IgG. In contrast, the levels of heat shock proteins HSP60 and HSP70 were significantly reduced in the plasma of all donor groups compared to the reference group, which could indicate possible abnormalities in the mechanisms of stress response after COVID-19. Conclusions. Our results suggest that prolonged immune activation, inflammation, and angiogenesis-related pathways play a crucial role in the pathogenesis of post-COVID-19 complications, underscoring the need for therapeutic strategies to address chronic inflammation, endothelial dysfunction, and impaired tissue recovery.